Maternal Smoking and Developmental Changes in Luteinizing Hormone (LH) and the LH Receptor in the Fetal Testis - Fowler, Paul A. (The Endocrine Society, 2009)
Context: The LH receptor (LHCGR) drives fetal testosterone secretion, which is vital for human masculinization. Maternal smoking is associated with defective masculinization, but the relationship between smoking, tropic hormones, testosterone, and functional LHCGR expression is poorly understood. Objective: This study aimed to investigate developmental changes in fetal gonadotropins, human chorionic gonadotropin (hCG), and expression of fetal testicular LHCGR isoforms and the effects of maternal cigarette smoking. Design: We conduced an observational study of the male fetus, comparing pregnancies in which the mothers did or did not smoke. Setting: The study was conducted at the Universities of Aberdeen and Glasgow. Patients/Participants: Testes and blood were collected from 54 morphologically normal human male fetuses of women undergoing elective termination of normal second-trimester pregnancies. Main Outcome Measures: We measured circulating testosterone, hCG, LH, prolactin, FSH, and testicular LHCGR isoform expression. Results: Fetal testosterone and hCG, but not LH, significantly declined between 11 and 19 wk gestation with no significant change in testicular responsiveness. The proportion of nonfunctional LHCGR transcript in fetal testes was 2.3-fold lower than in adults. Fetal hCG was reduced 38% (P = 0.021) and the ratio of inactive vs. active LHCGR isoforms lowered by smoking. Conclusions: Falling second-trimester fetal testosterone is probably due to declining maternal hCG because Leydig cell LH/hCG responsiveness remains constant. Although maternal cigarette smoking reduces fetal hCG, the ratio of inactive LHCGR isoforms is reduced and gonadotropin drive maintains testosterone production near control levels. The lower relative abundance of inactive isoforms compared with the adult testis reflects the importance of LHCGR.